The labor market consequences of gender differences in job search - Stefan Eriksson; Jonas Lagerström (Uppsala University, Department of Economics, 2008)
This paper studies gender differences in labor market outcomes using data from an Internetbased CV database. The women in the database get fewer firm contacts than men, and we show that this is partly explained by differences in education, experience and other skills, is not explained by differences in occupation and place of residence, and to a large extent is explained by differences in geographical search area. When we take into account differences in search area, the negative gender effect disappears. However, the results differ somewhat across subgroups: For highly skilled women a negative gender effect remains.
urn:nbn:se:uu:diva-86665
Keywords: J61; J71; 330; Job Search; Gender Differences; Discrimination; Arbeitsuche; Arbeitsmarktdiskriminierung; Frauen; Qualifikation; Räumliche Verteilung; Schweden